New Insights on Dietary Polyphenols for the Management of Oxidative Stress and Neuroinflammation in Diabetic Retinopathy - Gustavo Bernardes Fanaro; Marcelo Rodrigues Marques; Karin da Costa Calaza; Rafael Brito; André Moreira Pessoni; Henrique Rocha Mendonça; Deborah Emanuelle de Albuquerque Lemos; José Luiz de Brito Alves; Evandro Leite de Souza; Marinaldo Pacífico Cavalcanti Neto (MDPI AG, 2023)
Diabetic retinopathy (DR) is a neurodegenerative and vascular pathology that is considered one of the leading causes of blindness worldwide, resulting from complications of advanced diabetes mellitus (DM). Current therapies consist of protocols aiming to alleviate the existing clinical signs associated with microvascular alterations limited to the advanced disease stages. In response to the low resolution and limitations of the DR treatment, there is an urgent need to develop more effective alternative therapies to optimize glycemic, vascular, and neuronal parameters, including the reduction in the cellular damage promoted by inflammation and oxidative stress. Recent evidence has shown that dietary polyphenols reduce oxidative and inflammatory parameters of various diseases by modulating multiple cell signaling pathways and gene expression, contributing to the improvement of several chronic diseases, including metabolic and neurodegenerative diseases. However, despite the growing evidence for the bioactivities of phenolic compounds, there is still a lack of data, especially from human studies, on the therapeutic potential of these substances. This review aims to comprehensively describe and clarify the effects of dietary phenolic compounds on the pathophysiological mechanisms involved in DR, especially those of oxidative and inflammatory nature, through evidence from experimental studies. Finally, the review highlights the potential of dietary phenolic compounds as a prophylactic and therapeutic strategy and the need for further clinical studies approaching the efficacy of these substances in DR management.